1992
DOI: 10.1093/infdis/166.6.1316
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against IgAl Protease Are Stimulated Both by Clinical Disease and Asymptomatic Carriage of Serogroup A Neisseria meningitidis

Abstract: IgA1 protease was purified from a strain of serogroup A Neisseria meningitidis subgroup IV-1, representative of bacteria that caused an epidemic of meningococcal meningitis in The Gambia in 1982-1983. ELISAs and immunoblot assays were done using this protease as antigen with paired acute- and convalescent-phase sera from patients from that epidemic and from one in Finland caused by other serogroup A meningococci. Paired sera were also tested from healthy Gambians who were persistent nasopharyngeal carriers, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Another report showed that the secretion of this protease seems not to be required for the adherence and invasion of epithelial cells by N. gonorrhoeae in vitro (72). On the other hand, IgA1 protease activity can be inhibited by antibodies (161), and antibodies to IgA1 protease and inhibitory antibodies have been detected in serum and secretions from patients infected with IgA1 protease-producing organisms (48,103). Hedges et al (193) examined the levels of these opposing factors (IgA1 protease and inhibitory antibodies) in genital tract secretions and sera from women infected with N. gonorrhoeae, and their results suggested that cleavage of IgA1 by gonoccocal IgA1 protease within the lumen of the lower genital tract is unlikely to be a significant factor in the pathogenesis of infection by N. gonorrhoeae.…”
Section: Iga1 Proteasesmentioning
confidence: 99%
“…Another report showed that the secretion of this protease seems not to be required for the adherence and invasion of epithelial cells by N. gonorrhoeae in vitro (72). On the other hand, IgA1 protease activity can be inhibited by antibodies (161), and antibodies to IgA1 protease and inhibitory antibodies have been detected in serum and secretions from patients infected with IgA1 protease-producing organisms (48,103). Hedges et al (193) examined the levels of these opposing factors (IgA1 protease and inhibitory antibodies) in genital tract secretions and sera from women infected with N. gonorrhoeae, and their results suggested that cleavage of IgA1 by gonoccocal IgA1 protease within the lumen of the lower genital tract is unlikely to be a significant factor in the pathogenesis of infection by N. gonorrhoeae.…”
Section: Iga1 Proteasesmentioning
confidence: 99%
“…IgA1 proteases represent a group of structurally diverse enzymes-metalloproteases, serine-type proteases, and cysteine-type proteases-with different enzymatic mechanisms. Evidence of in vivo production of IgA1 proteases in human infections (4 -6), the association of recovery from infection with the development of Abs to IgA1 proteases (7)(8)(9), and the failure of related but nonpathogenic species of bacteria to produce IgA1 proteases (10,11) all point to IgA1 proteases being important virulence factors of the pathogens that produce them. Despite these persuasive indirect observations, the in vivo roles of IgA1 proteases in virulence are difficult to determine, because the substrate is restricted almost exclusively (12)(13)(14)(15) to IgA1 of humans, gorillas, and chimpanzees, and IgA of orangutans (16), and therefore convenient animal models are not available.…”
mentioning
confidence: 99%
“…Additional evidence that IgA1 proteases are involved in virulence comes from observations that the amount of enzyme secreted is directly related to the pathogenicity of the isolate (6); strains of related species that do not produce IgA1 protease are nonpathogenic (7,8); the products of IgA1 cleavage are detectable in the CSF, vaginal washings, and other body fluids of patients infected with an IgA1 protease-producing strain (9 -11); and Ab to the IgA1 protease is found in convalescing patients recovering from infection with an IgA1 protease-producing pathogen (12)(13)(14). However, because the substrate for IgA1 proteases is restricted almost exclusively (15)(16)(17) to IgA1 from human, gorilla, chimpanzee, and the IgA of the orangutan (18), it is difficult to prove that IgA1 proteases are virulence factors in vivo.…”
mentioning
confidence: 99%